2018
DOI: 10.3744/snak.2018.55.5.401
|View full text |Cite
|
Sign up to set email alerts
|

System Identification and Pitch Control of a Planing Hull Ship with a Controllable Stern Intercepter

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License(http://creativecommons.org/licenses/by-nc/3.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Planing hull type ships are often equipped with interceptor or trim tab to improve the excessive trim angle which leads to poor resistance and sea keeping performances. The purpose of this study is to design a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…We compared the resistance reduction rates of these two energy-saving appendages in waves against variations in wavelength and wave steepness, summarised the alterations in the heave and pitch transfer functions post-stern appendage installation, and assessed the ship resistance and motion change mechanisms from a flow field perspective. The following conclusions are outlined: (1) For the BH at wave steepness ak = 0.075, the added resistance coefficient increases and then diminishes as the wavelength increases. At λ/LPP = 1.5, the green water phenomenon occurs on the BH deck, leading to an added resistance peak of 70.6%.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…We compared the resistance reduction rates of these two energy-saving appendages in waves against variations in wavelength and wave steepness, summarised the alterations in the heave and pitch transfer functions post-stern appendage installation, and assessed the ship resistance and motion change mechanisms from a flow field perspective. The following conclusions are outlined: (1) For the BH at wave steepness ak = 0.075, the added resistance coefficient increases and then diminishes as the wavelength increases. At λ/LPP = 1.5, the green water phenomenon occurs on the BH deck, leading to an added resistance peak of 70.6%.…”
Section: Discussionmentioning
confidence: 90%
“…Here, φ denotes the predefined fluid properties of the given phases. The density and viscosity of water and air can be expressed as (1 ) (1 )…”
Section: Free Surface Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Z h f (n) means the lift generated by the thrust and hydrofoil interaction. Considering the thrust and hydrofoil lift, the net pitch moment by the waterjet operation can be defined as Equation (7). Since two terms are function of n m , the pitch motion of the vehicle can be controlled by changing n m .…”
Section: Impeller Rrevolution and Pitch Momentmentioning
confidence: 99%
“…They designed control systems based on a linear quadratic regulator (LQR) controller and showed the application of a controlled stern interceptor reduced pitch and heave to have reductions of up to 25% and 20%, respectively. Choi et al [7] identified the pitch dynamics model of a planing hull that includes a stern interceptor capable of active control by performing model tests in regular waves. They designed a controller that controls the attitude of the ship and verified the effectiveness of active control through towing tank experiments.…”
Section: Introductionmentioning
confidence: 99%